An ethical decalogue for the reintroduction of species to urban habitats (UNED Research Journal, 2018)
Reintroduction of species to their former habitats -after they have been built upon- will become more important as urbanization increases worldwide, but it should follow ethical guidelines. Here I propose ten guidelines that exclude species that threaten human life, health and property; protect organisms from significant suffering; provides them with proper habitat and assistance; includes experimental protocols, and is based on information gathered according to scientific standards
Keywords: ethical relationship with nature; cities as ecosystem; ecosystem restoration; humane treatment of organisms